Nitrogen Reduction and Organic Fertiliser Application Benefits Growth, Yield, and Economic Return of Cotton - Huangcheng He; Xuemei Lou; Jianguo Liu (Agriculture, 2024)
The application of excessive nitrogen fertiliser has been found to have a detrimental impact on the growth and development of cotton in Xinjiang, China. This has resulted in a reduction in cotton yield and economic benefit. The aim of this study was to investigate the potential for reducing the input of inorganic N fertiliser while maintaining the quality and yield formation of cotton. The objective of this study was to examine the growth, photosynthesis, and yield of cotton crops subjected to varying fertiliser treatments. The experiment was conducted in 2021–2022 with eight treatments in the experiment: no fertiliser (CK); conventional application of inorganic nitrogen fertiliser (T0); T1–T3, with 8%, 16%, and 24% reduction in inorganic nitrogen fertiliser application, respectively; and T4–T6, with organic fertilisers replacing the reduced inorganic nitrogen fertiliser application of T1–T3, respectively. In comparison to T0, T5 demonstrated the most notable agronomical performance and yield components across both years. This is attributable to the spatial distribution of cotton bolls, which was more conducive to the net photosynthetic rate and yield formation. This, in turn, led to an augmented photosynthetic capacity, enhanced biomass accumulation, and an elevated harvesting index. The results of the economic benefit analysis demonstrated that in comparison to the control treatment (T0), the net profit of all treatments except T3 increased. In conclusion, the economic benefit reached its maximum in the range of a 9.90–14.10% reduction in nitrogen and a 16.60–17.60% substitution of organic fertiliser.